Mexican natural resources management and biodiversity conservation - Azuz-Adeath, Isaac; Cuevas Corona, Alejandra (Springer, 2018)
This chapter shows the influence and potential impacts of decadal climate variability on Mexico’s coastal biodiversity, fishery, and agricultural production, using the temporal structure of several modes of climate variability relevant for the northern hemisphere, the Atlantic Multidecadal Oscillation (AMO), the Pacific Decadal Oscillation (PDO), and the North Atlantic Oscillation (NAO), as well as climatic variables time series (precipitation, maximum, and minimum temperature). An evaluation of the historical and potential effects of this natural climate variability is presented for the 17 Mexican coastal states. The results show a clear influence of the climatic variables and the different modes of climatic variability on the agricultural production in all coastal states, with the highest positive correlation between AMO and lemon production in Colima state (r = 0.87) and maximum negative between NAO and sorghum production in Tamaulipas state (r = −076); an influence on forestry production for some coastal regions – like Oaxaca state; as well as its impact on the natural vegetation cover changes and consequently on biodiversity. The need for systematic, regular, and long-term monitoring processes of climatic variables, coastal resources of economic value, and biodiversity are key elements for generating knowledge and establishing adaptation and mitigation measures for climatic phenomena of the order of decades and larger time scales.
Potential impacts of decadal climate variability on coastal biodiversity and societal important productive activities: a case study in mexican coastal states
Keywords: Climatic variability; Agricultural production; Decadal behavior; Biodiversity; Sistemas